AKTIVITAS ANTIJAMUR EKSTRAK ETANOL 50% DAN ETANOL 96% DAUN PACAR KUKU Lawsonia inermis L TERHADAP Trichophyton mentagrophytes - Oom Komala; Yulianita .; Fuji Raka Siwi (EKOLOGIA, 2019)
Trichopyton mentagrophytes is a type of fungus that belongs to a group of dermatophytes, and a disease that causes dermatophytosis (ringworm), this fungus likes parts that contain keratin substances such as skin, hair / hair, nails or horns. This study aims to determine the antifungal activity of 50% and 96% ethanol extract. KHM testing was made with a concentration of 2.5%, 5%, 7.5% and 10% with the dilution method to determine KHM. Whereas in testing the width of the inhibitory area (LDH) was carried out after getting the MIC value at concentrations of 10%, 25% and 50% with disc diffusion method to determine the effective LDH and qualitative phytochemical testing. The results showed that 96% ethanol solvent at a concentration of 50% could inhibit the fungus Trichopyton mentagrophytes compared to 50% ethanol as seen from the inhibition zone formed in the width of the inhibitory area. Secondary metabolite compounds found in 50% ethanol extract and 96% ethanol are flavonoids, alkaloids, saponins, tannins, quinones and terpenoids.